Behaviour of captive Ostrich chicks from 10 days to 5 months of age - Amado, Marina Freire (2011)
The behaviour of ostrich chicks bred in captivity was studied by using groups with 30 birds in five age groups: from 10 to 40 days of age; from 41 to 60 days of age; from 61 to 90 days of age; from 91 to 120 days of age and from 121 to 150 days of age. Six birds at each age were ringed around one of their feet and observed for four consecutive days for eight hours daily in three periods (in the morning, at noon and in the afternoon), following the "one-zero" method for sampling. The order for observation of behaviour of the six selected birds was performed randomly at every thirty minutes, totalling 16 periods or 80 minutes/bird/day. Fourteen types of behaviour were observed. There were differences among ages for behaviour like standing, walking, running, ingesting stones, ingesting feces, picking and attacking. Non-parametric-tests were used to analyse the behaviour according to age of the bird and to the periods of the day. There was a statistical difference between in the morning and at noon periods on behaviours standing, walking, eating ration and in litophagia, which were observed more frequently at the first hours of the day. When periods of the morning and afternoon were compared, the birds' age had a significant effect on behaviour sand bathing. When the periods noon/afternoon were compared, the behaviours which presented significant differences were walking, running, drinking water, eating ration, litophagia, coprophagia, dancing, sand bathing, whose occurrence was the highest during dusk. It was observed that the behaviour of young ostriches diverge according to the age and to day period.